Adsorption of basic dyes from aqueous solution by Nypa Fruticans Frond (NFR) - Iffah Nabihah Mhd Hassan Zaini (School of Environmental Engineering, University Malaysia Perlis, 2012)
In this study, the potential use of Nypa fruticans (NF) frond as the biosorbent for the removal of Methylene Blue (MB) (basic dye), Brilliant Green (BG) (basic dye) and mixture of Methylene Blue and Brilliant Green (MIX) was investigated. The effects of adsorption time, adsorbent dosage, particle size and initial dye concentration on NF frond adsorption for MB, BG and MIX dyes were investigated during the batch adsorption study. The results indicated that the amount of dye adsorbed on the NF frond increased with increasing initial dye concentration, adsorbent dosage and adsorption time. For MB, BG and MIX adsorption rate is optimal at adsorbent size 150 micrometres, adsorption period as long as 120 min, adsorbent dose and 600 mg/L initial dye concentration. The Langmuir and Freundlich adsorption models were used to evaluate the isotherm constants. The equilibrium data for all dye fitted very well with Langmuir Isotherm equation giving maximum monolayer adsorption capacity as high as 150.29 mg/g, 101.85 mg/g and 73.16 mg/g for MB, BG and MIX dyes, respectively. The modeling of the kinetics of dyes adsorption onto NF frond was investigated using pseudo-first order model and pseudo-second order model. The MB, BG and MIX dyes fitted well with the pseudo-second order. For column adsorption for MB and BG removal, the potential use of NF frond was investigated. The effect of flow rate, initial dye concentration and bed height on NF frond adsorption of MB and BG dye, were investigated during the column adsorption study. The results indicate that the column adsorption capacity of MB and BG removal decreased with increasing of dye concentration and flow rate. For MB and BG adsorption rate is most optimal in 5 mL/min flow rate, 12 cm bed height and 500 mg/L initial dye concentration. The column adsorption capacity is recorded as high as 492.00 mg/g for MB removal and 396.00 mg/g for BG removal.